The emerging role of nutritional support in the supportive care of pediatric patients undergoing hematopoietic stem cell transplantation - Muratore, Edoardo; Leardini, Davide; Baccelli, Francesco; Venturelli, Francesco; Cerasi, Sara; Zanaroli, Andrea; Lanari, Marcello; Prete, Arcangelo; Masetti, Riccardo; Zama, Daniele (Frontiers in Nutrition, 2023)
Allogeneic Hematopoietic Stem Cell Transplantation (allo-HSCT) represents a potentially curative strategy for many oncological, hematological, metabolic, and immunological diseases in children. The continuous effort in ameliorating supportive care represents one of the cornerstones in the improvement of outcome in these patients. Nowadays, more than ever nutritional support can be considered a key feature. Oral feeding in the early post-transplant period is severely impaired because of mucositis due to conditioning regimen, characterized by, mainly by vomiting, anorexia, and diarrhea. Gastrointestinal acute graft-versus-host-disease (GvHD), infections and associated treatments, and other medications, such as opioids and calcineurin inhibitors, have also been correlated with decreased oral intake. The consequent reduction in caloric intake combined with the catabolic effect of therapies and transplantation-related complications with consequent extended immobilization, results in a rapid deterioration of nutritional status, which is associated with decreased overall survival and higher complication rates during treatment. Thus, nutritional support during the early post-transplantation period becomes an essential and challenging issue for allo-HSCT recipients. In this context, the role of nutrition in the modulation of the intestinal flora is also emerging as a key player in the pathophysiology of the main complications of HSCT. The pediatric setting is characterized by less evidence, considering the challenge of addressing nutritional needs in this specific population, and many questions are still unanswered. Thus, we perform a narrative review regarding all aspects of nutritional support in pediatric allo-HSCT recipients, addressing the assessment of nutritional status, the relationship between nutritional status and clinical outcomes and the evaluation of the nutritional support, ranging from specific diets to artificial feeding.